2022
DOI: 10.1177/27526461221092429
|View full text |Cite
|
Sign up to set email alerts
|

Determining factors of access and equity in higher education: A systematic review

Abstract: This literature review study aims to provide an overview of influencing factors of access to and equity in higher education. In this way, the research offers insight into specific factors that support or hinder access and equity, respectively. Forty factors from thirty-three peer-reviewed articles, mostly from three continents: Europe, Australia, and America, published between 2014 and 2018, were selected for further analysis. The articles were analyzed into four organizational levels: government, university, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Equity addresses the fact that it might not be fair to provide all students with the same resources and support for learning (Maringe and Sing 2014) because students from disadvantaged backgrounds, especially low-SES students, need more guidance and support before and after they are accepted by the university. A literature review by Wanti et al (2022) revealed that social factors are crucial for both HE access and equity, which we explore further in the present study. Our investigation of access is especially focussed on the social factors influencing students before they are accepted by the university, while our equity focus explores the role of social factors after students have been accepted and during their learning process at the university.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Equity addresses the fact that it might not be fair to provide all students with the same resources and support for learning (Maringe and Sing 2014) because students from disadvantaged backgrounds, especially low-SES students, need more guidance and support before and after they are accepted by the university. A literature review by Wanti et al (2022) revealed that social factors are crucial for both HE access and equity, which we explore further in the present study. Our investigation of access is especially focussed on the social factors influencing students before they are accepted by the university, while our equity focus explores the role of social factors after students have been accepted and during their learning process at the university.…”
Section: Introductionmentioning
confidence: 89%
“…Data were collected via semi-structured interviews to explore the participants’ thoughts about the topic. The interview scheme was designed based on our prior review study (Wanti et al, 2022) about access and equity in HE. Several steps were followed to build the questions for the interviews:(i) creating an overview of the determining factors of access and equity in HE from our first study;(ii) changing these factors into questions to obtain clear statements from the respondents on whether they agree or disagree with the factors; for example, ‘do you agree that family plays a role in access to HE?’.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher education accrues enormous benefits both to a country in general and to the individual graduate in particular (Wanti et al, 2022). This makes fair regional representation in higher education imperative.…”
Section: Statement Of the Problemmentioning
confidence: 99%